Differentiating overlapping symptoms of vulvodynia and pudendal neuralgia. Issue 1 (February 2019) - Ghizzani, Anna; Carta, Serafino; Casoni, Annalisa; Ferrata, Paolo; Luisi, Stefano; Fortina, Mattia
Context: Vulvodynia is defined as a chronic vulvar pain non-associated with infectious, inflammatory, neoplastic or hormonal disorders. Objectives: To present a case demonstrating the difficulty in assessing concomitant disease in vulvodynia. Methods: A 26-year-old woman, presented with persistent vulvodynia. She received oral and topical medications and behavioural interventions to lessen sexual pain and restore sexuality. As sexual pain decreased, the patient reported symptoms previously not mentioned: continuous, intense periclitoral pain and numbness at the perineum when sitting for a long time. These new symptoms suggest the involvement of the peripheral neural system. The physical evaluation confirmed right-side pelvic distortion, and pathological increase in lumbar lordosis, which caused neuralgia radiating to the external genitalia and perineum, and overlapping with sexual pain. After diagnosing pudendal neuralgia according to the Nantes criteria, physical treatment and relaxation exercises to de-contract the spine were added to the vulvodynia regimen. Results: During treatment, vulvodynia was sometimes present but never unbearable, allowing satisfactory sex. With physical therapy, the symptoms of pudendal neuralgia decreased. Conclusion: Differentiating the presence of two conditions with overlapping symptoms is difficult because the vestibular pain had shadowed pudendal neuralgia symptoms at initial assessment. Syndromes of chronic pain tend to associate with each other and one syndrome may shadow symptoms of the concomitant condition affecting adjacent anatomical areas. Only the accurate identification of all the syndromes involved allows adopting the correct treatment.